2009
DOI: 10.1577/t07-090.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transportation and Other Factors on Survival Estimates of Juvenile Salmonids in the Unimpounded Lower Columbia River

Abstract: We estimated the survival of juvenile salmonids out-migrating through the lower Columbia River to the Pacific Ocean. We tested the null hypotheses that no association exists between survival and transportation type (including barge transportation and in-river migration with no transportation), release date, river flow, mean body weight, and tag type. During 2002-2004 and fall Chinook salmon Oncorhynchus tshawytscha and steelhead O. mykiss were implanted with uniquely coded radio or acoustic transmitter tags an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Within rivers and basins, telemetry has proven to be an essential tool for assessing fish survival and movement patterns (Jepsen et al 1998;Skalski 1998;Plumb et al 2006). In the Columbia River, scientists have identified acoustic telemetry as being an essential technology for observing the behavior and estimating the survival of juvenile salmonids passing through the side channels and the main stem FCRPS (Faber et al 2001;McComas et al 2005;Ploskey et al 2007;Ploskey et al 2008;Clemens et al 2009). Hydroelectric dams provide various routes of passage where mortality becomes pathway-specific depending on the physical properties of the technical installation (Coutant and Whitney 2000;Muir et al 2001;Skalski et al 2002;Weiland et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Within rivers and basins, telemetry has proven to be an essential tool for assessing fish survival and movement patterns (Jepsen et al 1998;Skalski 1998;Plumb et al 2006). In the Columbia River, scientists have identified acoustic telemetry as being an essential technology for observing the behavior and estimating the survival of juvenile salmonids passing through the side channels and the main stem FCRPS (Faber et al 2001;McComas et al 2005;Ploskey et al 2007;Ploskey et al 2008;Clemens et al 2009). Hydroelectric dams provide various routes of passage where mortality becomes pathway-specific depending on the physical properties of the technical installation (Coutant and Whitney 2000;Muir et al 2001;Skalski et al 2002;Weiland et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We take our estimate of SE from Muir et al (2006), who estimated migration survival of spring Chinook smolts in six years (1997)(1998)(1999)(2000)(2001)(2002) . A later study of survival in the Columbia River below Bonneville indicated that survival was quite variable (Clemens et al 2009). Sub-yearlings arrive in the estuary during spring and summer, after which we apply ocean survival, S OC,0 from summer to fall.…”
Section: Snake-lg-survival Of Marked Juveniles Tomentioning
confidence: 99%
“…Acoustic telemetry has become a commonly used tool for monitoring migratory patterns, habitat preferences and survival of fish [1][2][3]. Telemetry studies utilize an array of cabled and autonomous receivers to detect acoustic signals emitted by acoustic transmitters for tracking the location of fish in the river [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Telemetry studies utilize an array of cabled and autonomous receivers to detect acoustic signals emitted by acoustic transmitters for tracking the location of fish in the river [1][2][3]. These acoustic transmitters are implanted, either externally or internally, on the species of interest.…”
Section: Introductionmentioning
confidence: 99%